Predictive variables for half-Ironman triathlon performance - Gilinsky, N.; Hawkins, K. R.; Tokar, T. N.; Cooper, J. A. (Journal of Science and Medicine in Sport, 2014)
Objectives: To examine the relationship between training, anthropometric characteristics, tapering, and time performance for a half-Ironman distance race. Design: Cross sectional study in triathletes. Methods: Data were obtained for 209 participants (155 males; 54 females) competing in a half-Ironman triathlon. Participants provided information regarding triathlon experience, training, race preparation, and tapering. Participants were divided into three groups based on finish time for analysis. Results: Males in the fastest group weighed less and had lower body fat percentage compared to males in the slower groups (p ? 0.01). Athletes in the fastest group had completed more half-Ironman races and took fewer rest days during training compared to athletes in the slower groups (p < 0.01). The average time spent training was 13.9 ± 5.4 h per week, and this did not differ between groups. The faster group of athletes set lower race time goals (p < 0.01) and placed greater importance on achieving goal time (p = 0.04). Eighty-one percent reported performing a taper with a decrease in training volume of 58.5 ± 34.7% and a decrease in training intensity of 44.9 ± 40.8%. However, there were no differences in taper variables between the three groups. Age, previous best half-Ironman time, goal time, and goal importance predicted 58% of variance in finish time. Conclusions: The fastest group of triathletes exhibited differences in anthropometrics, race experience, and goal-setting compared to slower athletes. There were no differences in total training hours or tapering between groups. The best predictors of race performance were age, previous best half-Ironman time, goal time, and importance of reaching this goal.